Historical and linguistic studies in literature related to the New Testament: First series: Texts - Young, Edward J. (Published by the University, 1901)
Vol. 1. The book of Thekla -- The martyrdom of Cyprian and Justa -- The Epistle of Pelagia -- An Ethiopic manuscript of John's gospel -- Ethiopic manuscripts from the collection of Wilberforce Eames.